Development Learning Media E-Book Based on TPACK on Natural Science Education in Elementary School - Selsa Ramdhania Putri (Indonesian Journal of Learning Education and Counseling, 2022)
Development research aims to instill the character value of responsibility in students during this pandemic, this is one of the backgrounds for the development of this Digital Picture Storybook. In addition, the problem that is often faced is the limited learning media available to instill the character of responsibility in children. The purpose of this study was to 1) find out the steps for developing digital picture story books to increase the character of responsibility, 2) find out the feasibility of digital picture story book media to improve the character of responsibility in 3rd grade elementary school students. This research and development model adopts the 4D theory (four-D model). The steps for developing digital illustrated storybooks that have been carried out are the Define, Design, and Develop stages. The method used is Research & Development, the model developed using; Analyze, Design, Develop, Implement, and Evaluation (ADDIE). The steps in this research stage, 1) analyzing research needs, 2) product design, 3) developing products, 4) student trials, and 5) evaluation. Data analysis techniques using interviews, and questionnaires.